Perpendicular Magnetic Anisotropy on W-based Spin-Orbit Torque CoFeB | MgO MRAM Stacks. Issue 1729 (2015) - Kaidatzis, Andreas; Psycharis, Vasileios; García-Martín, José Miguel; Bran, Cristina; Vázquez, Manuel; Niarchos, Dimitrios
ABSTRACT: We study W | Ta | CoFeB | MgO stacks for spin-orbit torque MRAM applications. A strong perpendicular magnetic anisotropy is obtained after annealing for CoFeB layer thickness of 0.9 nm or 1.2 nm and for specific W/Ta ratios, were the Ta layer thickness is between 0.3 nm and 1 nm. Furthermore, the desired high-spin orbit coupling β-phase of W is preserved even after annealing at 350 ° C. We argue that an efficient B getter, like Ta, is necessary for the coherent crystallization of the CoFeB | MgO interface that allows for the establishment of perpendicular magnetic anisotropy.